Russian Approaches to International Law - Mälksoo, Lauri (Oxford University Press, 2015)
This book examines Russian approaches to international law from three different yet closely interconnected perspectives: history, theory, and recent state practice. The study uses comparative international law as a starting point and argues that in order to understand post-Soviet Russia's state and scholarly approaches to international law, one should take into account the history of ideas in Russia. To some extent, Russian understandings of international law differ from what is considered the mainstream in the West. One specific feature of this work is that it goes inside the language of international law as it is spoken and discussed in post-Soviet Russia, especially the scholarly literature in the Russian language, and relates this literature to the history of international law as discipline in Russia. Recent state practice such as the annexation of Crimea in 2014, Russia's record in the UN SC, the European Court of Human Rights, investor-state arbitration, and the creation of the Eurasian Economic Union are laid out and discussed in the context of increasingly popular 'civilizational' ideas, i.e. the claim that Russia is a unique civilization and not part of Europe understood as the West. The implications of this claim for the future of international law, its universality and regionalism are discussed. This study concludes the author's five-year work on ERC-funded grant that enabled him to attend international law conferences in Russia and other CIS countries, as well as get access to relevant sources that often cannot be so easily accessed in the West.